Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/febs.12957
|View full text |Cite
|
Sign up to set email alerts
|

Comparing crystal structures of Ca2+ATPase in the presence of different lipids

Abstract: The activity of the sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) depends strongly on the lipid composition of the surrounding membrane. Yet, structural information on SERCA-lipid interaction is still relatively scarce, and the influence of different lipids on the enzyme is not well understood. We have analyzed SERCA crystal structures in the presence of four different phosphatidylcholine lipids of different lengths and doublebond compositions, and we find three different binding sites for lipid head group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 41 publications
6
54
0
Order By: Relevance
“…13 and 17). Interestingly, crystal structures of Ca-ATPase prepared with different lipids also reveal three specific lipid binding sites in the pockets analogous to those proposed here for Na,KATPase (50). Another recent approach for detection of specific lipid binding to membrane proteins utilizes ion mobility mass spectrometry (51,52).…”
Section: Multiple Specific Lipid Binding Sites In Nak-atpasesupporting
confidence: 62%
“…13 and 17). Interestingly, crystal structures of Ca-ATPase prepared with different lipids also reveal three specific lipid binding sites in the pockets analogous to those proposed here for Na,KATPase (50). Another recent approach for detection of specific lipid binding to membrane proteins utilizes ion mobility mass spectrometry (51,52).…”
Section: Multiple Specific Lipid Binding Sites In Nak-atpasesupporting
confidence: 62%
“…Interestingly, residues in SERCA corresponding to some of these residues, i.e. T254, D258, and N550, together with the 'P+4' residue in M4 (Y618 in Dnf1p or F511 in Drs2p), are in proximity of a binding pocket for a phospholipid molecule identified in several E2 structures of SERCA1a [124,125], suggesting that this primordial lipid-binding site in P2-ATPases might have evolved into a site important for phospholipid translocation in P4-ATPases [32]. As those exit gate residues seem to discriminate di-acylated lipids from lysolipids, it seems likely that the ester linkage between the fatty acyl chain and the glycerol backbone is part of the lipid recognition pocket in P4-ATPases.…”
Section: Two-gate Mechanismmentioning
confidence: 99%
“…Further studies are needed to clarify the interplay between the solubilizing effect of lysophospholipids and their selective activating effect on the PM H ϩ -ATPase in planta. Several binding sites for lipids have been identified in crystal structures of the model P-type ATPase SERCA (35); of these, four do not appear to serve merely as crystal contacts and could represent tightly bound annular lipids. Of special note is the binding site near the calcium entrance pathway modeled as a phosphatidylethanolamine-binding site in the structures.…”
Section: Lysophospholipid Activation Of the Pm Hmentioning
confidence: 99%
“…PM Ca 2ϩ -ATPases are strongly activated by acidic phospholipids (29) and contain a binding site for acidic phospholipids that interfere with regulation by a calmodulin-binding terminal domain (30 -32). A phospholipid-binding site is apparent in crystal structures of SERCA (33)(34)(35), and it has been suggested that this site is conserved among distantly related P-type ATPases (36). Lysophosphatidylcholine (lyso-PC) is a detergent-like molecule produced from cleavage of phosphatidylcholine by the enzyme phospholipase A 2 and has been proposed to serve as a signaling molecule in plants (37)(38)(39).…”
mentioning
confidence: 99%